1990
DOI: 10.1111/j.1600-0749.1990.tb00287.x
|View full text |Cite
|
Sign up to set email alerts
|

Fast Atom Bombardment Mass Spectrometry in the Study of Dopamine Melanogenesis Intermediates

Abstract: Fast atom bombardment was applied to the study of the intermediates of the reaction dopamine-tyrosinase after treatment with diazomethane. The identification of trimethoxyindoline, dopamine-o-quinone and dimethoxyindole was easily achieved by this ionization method, together with accurate mass measurements and collision experiments. The structures of these compounds are in agreement with those already hypothesized in studies on melanogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1991
1991
2002
2002

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…In previous studies10,, 11 we applied electron impact (EI) and fast atom bombardment (FAB) mass spectrometry to structural analysis of the intermediates of melanogenesis, and confirmed the first steps of the Raper‐Mason scheme in which tyrosine is enzymatically converted to DOPA, dopaquinone, leucodopachrome, dopachrome, 5,6‐dihydroxindole (DHI), and then to indole‐5,6‐quinone, before forming melanin (Scheme ).…”
Section: Methodsmentioning
confidence: 64%
“…In previous studies10,, 11 we applied electron impact (EI) and fast atom bombardment (FAB) mass spectrometry to structural analysis of the intermediates of melanogenesis, and confirmed the first steps of the Raper‐Mason scheme in which tyrosine is enzymatically converted to DOPA, dopaquinone, leucodopachrome, dopachrome, 5,6‐dihydroxindole (DHI), and then to indole‐5,6‐quinone, before forming melanin (Scheme ).…”
Section: Methodsmentioning
confidence: 64%
“…16,17 Our previous studies, carried out by continuous-flow fast atom bombardment (FAB) mass spectrometry 18 of the intermediates of the reaction mixtures tyrosine-, Dopa-and dopamine-tyrosinase, showed that the formation of the orange chromophore (dopachrome from tyrosine or Dopa, aminochrome from dopamine), one of the intermediates of melanogenesis, was faster with dopamine than with Dopa or tyrosine. The production of melanogenesis intermediates from dopamine using tyrosinase as enzyme has also been confirmed by means of collisional spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…These ions had already been found by us in a study of dopamine melanogenesis intermediates carried out using a completely different approach, i.e., stopping the enzyme reaction at different times by methyla-tion with diazomethane. In that case, the ions at m/z 152 were identified as the protonated molecular species (EM + HI+) of dopamine quinone (Allegri et al, 1990) Coming back to the particularly abundant ionic species at m/z 149, and looking at the oxidative pathway for dopamine (Scheme 2), we see that differently structured compounds can lead to the formation of molecular ions at m/z 149, like aminochrome, present also as a quinone imine system, and 5,6-dihydroxyindole.…”
Section: Resultsmentioning
confidence: 99%
“…However, despite these studies, little is definitely known about the chemistry of the later stages of dopamine melanogenesis. In the last few years we have extensively employed mass spectrometric techniques in structural studies of melanins, analyzing directly the species of interest by collision spectroscopy (Allegri et al, 1987(Allegri et al, , 1988(Allegri et al, , 1990Emary et al, 1989).…”
Section: Introductionmentioning
confidence: 99%